How Innovations in Land Administration Reform Improve on Doing Business : Cases from Lithuania, the Republic of Korea, Rwanda and the United Kingdom - Hilhorst, Thea (World Bank, Washington, DC, 2015)
This note lays out the rationale for including land administration quality index in the standard ‘registering property’ indicator by doing business and discusses initial evidence from the global sample, showing that many countries, including some that have performed well on Doing Business’s traditional ranking, have a long way to go to establish a system of land administration that is reliable and transparent, achieves sufficient coverage, and minimizes disputes. The cases in this brochure document that by smartly deploying new technology, countries can make progress in this direction irrespective of their initial income level. Continued monitoring and learning from experience at all levels had an important role in facilitating such progress. Doing Business will contribute to this agenda by elevating the profile of land governance, tracking countries’ performance with respect to land administration quality index, and fostering global exchange and learning from good performers.